Perbandingan, Monoterapi, Double Terapi, Triple Kombinasi Terapi Pada Pasien Glaukoma Primer Sudut Terbuka Di Rumah Sakit Mata Lampung Eye Center - Syalsa Zaiva; Nisa Karima (CV. Jasa Sukses Abadi, 2026)
The eye is an essential sensory organ that delivers visual information to the brain. Glaucoma is a progressive optic neuropathy that can disrupt this process and lead to irreversible blindness. Primary open angle glaucoma is the most common type and is characterized by a gradual increase in intraocular pressure with minimal early symptoms. Glaucoma treatment is usually initiated with single drug therapy or monotherapy. If monotherapy is insufficient to control intraocular pressure, combination therapy using two or more medications is required, including double therapy and triple combination therapy. This study aimed to compare the effectiveness of monotherapy, double therapy, and triple combination therapy in reducing intraocular pressure in patients with primary open angle glaucoma at Lampung Eye Center Eye Hospital. An observational analytic method with a cross sectional design was used. Data on intraocular pressure and treatment regimens were obtained from medical records. Bivariate analysis was performed using the Kruskal Wallis test. The results showed that most subjects were male, with 23 patients or 53.5%, and the most common age group was 40 to 60 years, accounting for 41.9% of participants. Of the 43 patients included, 20.9% (9 patients) received monotherapy, 60.5% (26 patients) received double therapy, and 8 patients or 18.6% received triple combination therapy. Bivariate analysis demonstrated a statistically significant reduction in intraocular pressure in patients receiving triple combination therapy, with a p value less than 0.05. These findings indicate that triple combination therapy provides the most significant intraocular pressure reduction in patients with primary open angle glaucoma.